Transcriptional responses of Metarhizium pingshaense blastospores after UV-B irradiation - Corval, Amanda Rocha da Costa; Carvalho, Lucas Amoroso Lopes de; Mesquita, Emily; Fiorotti, Jéssica; Corrêa, Thaís Almeida; Bório, Victória Silvestre; Carneiro, Adriani da Silva; Pinheiro, Daniel Guariz; Coelho, Irene da Silva; Santos, Huarrisson Azevedo; Fernandes, Everton Kort Kamp; Angelo, Isabele da Costa; et al. (Frontiers in Microbiology, 2024)
Metarhizium is widely known for its role as an arthropod biocontrol agent and plant bioinoculant. By using mass-production industrial methods, it is possible to produce large amounts of fungal single-celled propagules (including blastospores) to be applied in the field. However, in the environment, the solar ultraviolet components (particularly UV-B) can harm the fungus, negatively impacting its pathogenicity toward the arthropod pest. The present study is the first to use comparative genome-wide transcriptome analyses to unveil changes in gene expression between Metarhizium pingshaense blastospores exposed or not to UV-B. Relative blastospores culturability was calculated 72 h after UV-B exposure and exhibited 100% culturability. In total, 6.57% (n = 728) out of 11,076 predicted genes in M. pingshaense were differentially expressed after UV-B exposure: 320 genes (44%; 320/728) were upregulated and 408 (56%; 408/720) were downregulated in the UV-B exposed blastospores. Results unveiled differentially expressed gene sets related to fungal virulence, production of secondary metabolites, and DNA repair associated with UV damage; genes related to virulence factors were downregulated, and genes associated with nucleotide excision repair were upregulated. These findings illustrate critical aspects of Metarhizium blastospores strategies to overcome UV-B damage and survive solar radiation exposures in insulated fields.